Chronic endometritis in recurrent implantation failure: Use of prednisone and IVF outcome. (September 2022) - Giulini, Simone; Grisendi, Valentina; Sighinolfi, Giovanna; Di Vinci, Pierluigi; Tagliasacchi, Daniela; Botticelli, Laura; La Marca, Antonio; Facchinetti, Fabio
Abstract: In recurrent implantation failure patients (RIF), the main criteria for diagnosis of chronic endometritis, is the presence of plasma cells CD138 + in endometrial biopsy. The aim of the present study was to evaluate if treatment with prednisone, in patients with RIF and chronic endometritis, improve IVF outcome. A retrospective study was performed between 2019 and 2020. A total of 27 patients with RIF and an endometrial biopsy positive for CD56 + cells were enrolled. The treatment with prednisone 10 mg per day is began together with controlled ovarian stimulation (COS). Among endometrial biopsies, 13 (48.14%) were positive also for CD138 cells, and an antibiotic treatment was added. In all patients, after therapy, in the subsequent IVF cycle, the clinical pregnancy rate was 25.9% and the live birth rate was 22.2%. Analysing pregnancies according to the percentage of CD 56 cells on endometrial biopsy, the live birth rate in the subgroup of patients with marked endometritis (defined by the presence of >10% CD56 + cells) was 29.41%, while in the subgroup with mild endometritis (CD 56 >5% and <10%) was 10%. In the subgroup with mild endometritis with CD 138 positive the live birth was 25%, while in patients with CD 138 negative no live birth were observed. In patients with RIF the count of at least two cell types (CD 138 and CD 56 cells) on endometrial biopsies is advisable. Our study suggests a benefit of prednisone and antibiotic treatment on live birth rate in a subsequent IVF cycle. Highlights: In reproductive medicine, one of the intriguing challenges is still to overcome the recurrent implantation failure (RIF). In RIF patients the count ofCD 138 and CD 56 cells on endometrial biopsies is advisable to diagnose chronic endometritis. In patients with RIF and chronic endometritis prednisone treatment could improve live birth rate in a subsequent IVF cycle.